Management of Complex Wounds with Fresh Cryopreserved Human Allografts - Landsman, DPM, PhD, Adam (North American Journal of Medicine and Science, 2010)
In this manuscript, we review the use of fresh cryopreserved human skin allografts for the treatment of complex wounds. The reasons why this technology has generated renewed interest, as well as some clinical outcomes are examined. Based on our experience, we feel that cryopreserved human skin allografts offer an effective, relatively inexpensive alternative for the treatment of complex wounds such as diabetic foot ulcers and venous leg ulcers.